The influence of civil servant competency dimensions on perceived usefulness and perceived ease of use of digital transformation - Fitri; Sofyan Bekkah; Lukman (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2026)
Digital transformation in local bureaucracy is determined not only by technological availability but also by the readiness of human resources who operate digital systems. In regional planning organizations, civil servant competency is a crucial factor because administrative work is cross-unit, data-driven, and requires rapid service delivery. This study analyzes the influence of civil servant competency dimensions motives, traits, self-concept, knowledge, and skills on perceived usefulness, the influence of perceived usefulness on perceived ease of use, and the mediating role of perceived usefulness in the relationship between competency and perceived ease of use. This research employed a quantitative approach with a cross-sectional design. Primary data were collected through a Likert-scale questionnaire administered to 60 civil servants selected using purposive sampling. The model was tested using Partial Least Squares Structural Equation Modeling to examine causal relationships and indirect effects among constructs. The results indicate that competency dimensions, particularly traits, self-concept, and knowledge, significantly contribute to the formation of perceived usefulness. Perceived usefulness also shows a strong relationship with perceived ease of use and functions as the pathway through which competency influences perceptions of system usability. In contrast, technical skills alone do not automatically increase perceived usefulness when they are not aligned with organizational workflows, routines, and user beliefs. These findings extend the application of the Technology Acceptance Model in the public sector by emphasizing the importance of adaptive characteristics, digital self-confidence, and literacy in policy and work processes to ensure the benefits of digital transformation are effectively realized in public organizations.